Information needs, accessibility and utilization of library information resources as determinantes of psychological well-being of prison inmates in Nigeria - Emasealu, Helen Uzoezi; Popoola, Sunday Olanrewaju (Faculdade de Filosofia e Ciências, 2016)
This paper investigated information needs, accessibility and utilization of library information resources as determinants of psychological well-being of prison inmates in Nigeria. Survey research design of the correlation type was adopted. The stratified random sampling was used to select 2875 inmates from the population of 4,823 in 12 prisons with functional libraries. A questionnaire titled Information need, accessibility, utilization and psychological well-being of Prison Inmates was used to collect data on the sampled 2875 inmates out of which 2759 correctly completed questionnaire resulting in a response rate of 95.34%, were used in data analysis. Data were analyzed using descriptive statistics of percentages, mean and standard deviation and inferential statistics of correlation analyses. The study found that there was significant multiple correlation among information needs, accessibility to library information resources, utilization of library information resources and psychological well-being of the inmates (r=0.665.p? 0.05). Also, there was significant relationship between: psychological well-being and accessibility to library information resources by prison inmates (r=0.438; p? 0.05); utilization of library information resources (r= .410; p?05), and information needs (r=.454; p? 05). Result also indicated that information needs, accessibility to library information resources and utilization of library information resources are very critical ingredients in determining the psychological well-being of prison inmates. Consequently, all stakeholders should endeavour to equip prison libraries with relevant and current information resources for improved psychological well-being of prison inmates